Determinants of Foreign Direct Investment in Romania: a Quantitative Approach - Calcedonia Enache; Fernando Merino (Amfiteatru Economic Journal, 2017)
This study aims to examine the dynamic relationship between foreign direct investments (FDI) and economic growth, using the Structural Vector Autoregressive model, in the period 2007-2014. The results of the econometric model show that the trajectory of FDI has its own origins, with reduced influences from economic growth. Another important conclusion is that there is a unidirectional causal relationship from the economic growth towards FDI, more precisely the influence of FDI on economic growth does not have a systematic, anticipatory nature. These results were achieved in the condition that, in the analyzed period, the net inflows of FDI were influenced by the lack of certainty on the sustainable re-launching of the economic growth both domestically and internationally, the segmentation of the financial market, the domestic structural reforms.
Keywords: C18; E43; F21; 330; foreign direct investment; economic growth; vector autoregressive model; Sims-Bernanke decomposition; Granger causality test